Accounting for biodiversity - Jones, Michael (London New York Routledge Taylor& Francis Group, 2014)
"'Biodiversity' at its simplest, refers to the variety of species inhabiting Planet Earth. It is essential to the well-being of the planet. There is now a scientific consensus around the current ongoing crisis in biodiversity arising from both climate change and human activities. Experts believe we are in the middle of a mass extinction of biodiversity with devastating consequences for our planet. Accounting for Biodiversity explores the need for companies to actively protect, conserve and improve biodiversity within their sphere of operation. The 14 chapters written by a selected team of experts investigate the ways in which companies are embracing their responsibility through a variety of biodiversity initiatives and innovative models designed to improve the recording, reporting and valuing of biodiversity. Global case studies look at biodiversity accounting in Africa, Asia, Australasia, Europe and South America. Overall, this book provides a comprehensive set of reflections on accounting for biodiversity and recommendations for the future. This book is essential reading for all those interested in the contribution that accounting can make to the preservation of accounting. As we see increasing awareness of the importance of sustainability and ecological responsibility in business activity it is relevant and should prove informative to students, managers, accountants and those in business more generally. It is also important for all those interested in conserving biodiversity. "--
"Accounting for Biodiversity explores the need for companies to actively protect, conserve and improve biodiversity within their sphere of operation. The 14 chapters written by a selected team of experts investigate the ways in which companies are embracing their responsibility through a variety of biodiversity initiatives and innovative models designed to improve the recording, reporting and valuing of biodiversity"--
Keywords: BUSINESS & ECONOMICS / Accounting / General; BUSINESS & ECONOMICS / Business Ethics; BUSINESS & ECONOMICS / Development / Sustainable Development; Social accounting; Biodiversity; Social responsibility of business